PERBANDINGAN KETEPATAN MENENDANG KEARAH GAWANG DENGAN MENGGUNAKAN KURA-KURA BAGIAN DALAM DAN KURA-KURA BAGIAN LUAR KELAS XI PUTRA SMA NEGERI 1 DOMPU TAHUN PELAJARAN 2018/2019: Indonesia - Ahmad Pratama, Sandi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2020)
The study purpose: The sport of football consists of various forms of movement and techniques in the game. Besides that, the understanding of kicking ball techniques properly and correctly has not been mastered so that beginners still seem to just kick without knowing what is obtained from the results of these kicks. Materials and methods: In this study the total population is 100 people taken from classes XI.A, XI.B, XI.C, XI.D and from this population will be sampled in conducting research. The sample used in this study is 20%, therefore the number of samples is 20% x 100 people and so the number of samples is 20 people. Based on this comparison, it shows that the t-test result or the t-count value is smaller than the t-table Results: